Promoting access to COVID-19 convalescent plasma in low- and middle-income countries. (February 2021) - Bloch, Evan M.; Goel, Ruchika; Montemayor, Celina; Cohn, Claudia; Tobian, Aaron A.R.
Abstract: Low- and middle-income countries (LMICs) remain neglected in the Coronavirus 19 (COVID-19) pandemic. COVID-19 convalescent plasma (CCP) (i.e. plasma collected from individuals after their recovery from COVID-19) has emerged as a leading medical treatment for COVID-19. Studies to date support the safety—and increasingly the efficacy—of CCP to treat COVID-19. This has motivated large-scale procurement and transfusion of CCP, notably in the United States (US), where inventories of CCP have been attained, and government-supported stockpiling of CCP is underway. CCP is a therapy that could be implemented in LMICs. However, systemic and transfusion-specific challenges (e.g. capacity for donor mobilization and collections) impede local procurement of this resource in sufficient volumes to meet clinical demand. This raises the question as to whether there are strategies to facilitate sharing of CCP with LMICs and/or bolstering local capacity for collection to contend with the health crisis. While compelling, there are cost-related, logistical and regulatory barriers to both approaches. For one, there is complexity in diverting national interest (e.g. in the US) away from an epidemic that displays few signs of abating. There are also concerns regarding equitable distribution of CCP in LMICs and how that might be overcome. Further, the barriers to blood donation in general apply to collection of CCP; these obstacles are longstanding, accounting for the inability of many LMICs to meet their blood transfusion needs. Nonetheless, CCP affords dual opportunity for humanitarian outreach while tackling a broader challenge of blood transfusion safety and availability.